Research on the Formation and Development of the Area Centred on Jiyu Gakuen, focusing on the founders’ Philosophy - Genda, Yuta; Nagano, Masayoshi; Nakajima, Naoto (International Planning History Society Proceedings, 2022)
In this study, we analyzed the formation and development of the area, focusing on the philosophy of those who created the area as one of the key points that led to the exposure, preservation, and transmission of cultural property values. The target area is centred on Jiyu Gakuen, located in Minamisawa, Higashikurume City, Tokyo. In Ikebukuro, the campus was created by the fusion between the philosophy of the couple of Motoko Hani and Yoshikazu Hani, the founder, and the architecture designed by Frank Lloyd Wright. Later, the philosophy was embodied through the school's social activities. After moving to Minamisawa, the new school town was built based on Hanis' philosophy. A multilayered community carried out the campus, the surrounding area, and the school town. The philosophy was developed into people who understood Hanis' philosophy. The architecture designed by Arata Endo, who understood Hanis' philosophy, became part of the area’s landscape. After WWII, the region's urbanization transformed the school from an entity with urban elements to one that preserved the original regional landscape. Education and architecture were passed on to the next generation, who understood the philosophy. In recent years, the developed philosophy was clearly stated: cultural heritage and clarification.